2022
DOI: 10.1155/2022/3750556
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding Teledentistry among Dental Professionals in Malaysia

Abstract: Objective. Teledentistry is considered to be a technological advancement in providing dental care to patients while effectively addressing the time management. Furthermore, the pandemic of COVID-19 has been here for quite long now, forcing the dental practitioners to ponder upon other methods of healthcare delivery apart from the traditional in-office direct clinical examination. The aim of this study was to explore the perceptions of dental professionals of Malaysia regarding teledentistry, which can act as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 40 publications
3
20
1
1
Order By: Relevance
“…Based on the research method, twentyone articles were cross-sectional study design, 13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] one article was cross-sectional with a mixed method design, 40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research method, twentyone articles were cross-sectional study design, 13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] one article was cross-sectional with a mixed method design, 40…”
Section: Resultsmentioning
confidence: 99%
“…Based on the research method, twenty-one articles were cross-sectional study design, 13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] one article was cross-sectional with a mixed method design, 40 and one article was a systematic review. 44 Based on the location of the study, five articles were conducted in India, 24,27,30,32,38 three articles in Pakistan, 16,31,34 three articles in Saudi Arabia, 28,29,36 two articles in Indonesia, 37,43 two articles in the United States, 25,40 and a few other articles in Australia, 26 Malaysia, 41,44 France, 39 Colombia, 13 and Brazil. 33 One article was conducted in two countries (Saudi Arabia and Pakistan) 42 and one article was a global study.…”
Section: Resultsmentioning
confidence: 99%
“… 24 Teledentistry is a technological advancement that can improve access to dental care services and enhance time management for dental practitioners and patients. 25 Although teledentistry is not a new discipline, the emergence of the COVID-19 pandemic has raised attention to its crucial role as a tool for delivering dental services without the risk of infection. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…They have struggled with the medicolegal issues concerned with Teledentistry practice especially in rural areas [60,61]. A whooping 70-80% majority of Malaysian dentists expressed uncertainty in the usefulness of Teledentistry in their country [62]. A nationwide study conducted in Brazil confirmed that their dentists were not adequately prepared to implement Teledentistry [63].…”
Section: Discussionmentioning
confidence: 99%